2015
DOI: 10.3402/meo.v20.27597
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the incidence and effect of major life events on graduate medical education trainees

Abstract: PurposeThis study aims to assess the incidence of major life events during graduate medical education (GME) training and to establish any associations with modifiable activities and career planning.MethodsThe authors surveyed graduating GME trainees from their parent institution in June 2013. Demographic information (clinical department, gender, training duration) and major life events (marriage, children, death/illness, home purchase, legal troubles, property loss) were surveyed. Respondents were queried abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that young physicians tend to opt for specialties that allow an optimal work-life balance (2) , (3) . In a study, about 30% of graduate medical trainees claimed that their career plans were influenced by life events (4) . In pioneering work published in 1990, Schwartz et al categorized medical specialties into “controllable lifestyle (CL)” specialties (such as anesthesiology, dermatology, emergency medicine, neurology, ophthalmology, otolaryngology, pathology, psychiatry, and radiology) and “noncontrollable lifestyle (NCL)” specialties (such as internal medicine, family practice, pediatrics, obstetrics/gynecology, and surgery) (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that young physicians tend to opt for specialties that allow an optimal work-life balance (2) , (3) . In a study, about 30% of graduate medical trainees claimed that their career plans were influenced by life events (4) . In pioneering work published in 1990, Schwartz et al categorized medical specialties into “controllable lifestyle (CL)” specialties (such as anesthesiology, dermatology, emergency medicine, neurology, ophthalmology, otolaryngology, pathology, psychiatry, and radiology) and “noncontrollable lifestyle (NCL)” specialties (such as internal medicine, family practice, pediatrics, obstetrics/gynecology, and surgery) (5) .…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 cross-sectional study of all residents and fellows at Duke University revealed that 96% of trainees sustained major life events, and 33% of trainees suffered the death of a close family member. 47 While no such study has been performed for practicing surgeons, it stands to reason that as we age, death and illness become more common. Often, we take for granted the health of our loved ones.…”
Section: Major Life Eventsmentioning
confidence: 99%
“…When life events related to physical or mental health, relationships, or family occur, there is little flexibility in the system to allow residents to attend to their needs. 21,26,27 Instead, residents who require time off for health or personal reasons must navigate a complex coverage system, which could include the redistribution of work to their peers. Moreover, requesting time away from work often necessitates disclosure of a mental or physical health concern or disability to their superiors, who are often the same individuals responsible for writing their letters of recommendation and advocating for them to future training programs or employers.…”
Section: Introductionmentioning
confidence: 99%